e-Marketing-based training for management of the Temiangan Hill tourism village in Lampung, Indonesia - Muhammad Zakaria; Riswandi; Herpratiwi; Zainal Abidin Ariefi (Lighthouse Publishing, 2022)
Study this aim for produce product in the form of training based on e-marketing for manager village tour temiangan hill in the district bungin West Lampung Regency , for develop area tour Temiangan Hill. Method data collection using documentation , observation and test and questionnaire . Effectiveness study show that the average N-Gain normalized 0.73 ( high ), 81 % attractiveness ( attractive ) and there is a significant average posttest and pretest scores i.e. 493>147 shows thit > ttable i.e. 21.44>2.36 with level significant t0.05 means showing that there is influence Among training based on e-marketing to village tour temiangan hill in Bung sub - district , West Lampung district with results enhancement knowledge and HR participants training West Lampung district .